In Vitro Assessment of the Genotoxic Potential of Pristine Graphene Platelets - Malkova, Andrea; Svadlakova, Tereza; Singh, Avni; Kolackova, Martina; Vankova, Radka; Borsky, Pavel; Holmannova, Drahomira; Karas, Adam; Borska, Lenka; Fiala, Zdenek (Nanomaterials (Basel, Switzerland), 2021)
(1) Background: Graphene is a two-dimensional atomic structure with a wide range of uses, including for biomedical applications. However, knowledge of its hazards is still limited. This work brings new cytotoxic, cytostatic, genotoxic and immunotoxic data concerning the in vitro exposure of human cell line to two types of graphene platelets (GP). It also contributes to the formation of general conclusions about the health risks of GP exposure. (2) Methods: In vitro exposure of a THP-1 cell line to three concentrations of two GP over 40 h. The cytotoxic potential was assessed by the measurement of LDH and glutathione (ROS) and by a trypan blue exclusion assay (TBEA); the cytostatic and genotoxic potential were assessed by the cytokinesis-block micronucleus (CBMN) test; and the immunotoxic potential was assessed by the measurement of IL-6, IL-10 and TNF-α. (3) Results: We found a significant dose-dependent increase in DNA damage (CBMN). The lowest observed genotoxic effect levels (LOGEL) were 5 µg/mL (GP1) and 30 µg/mL (GP2). We found no significant leaking of LDH from cells, increase in dead cells (TBEA), induction of ROS, increased levels of cytostasis, or changes in IL-6, IL-10 and TNF-α levels. (4) Conclusions: The genotoxicity increased during the short-term in vitro exposure of THP-1 to two GP. No increase in cytotoxicity, immunotoxicity, or cytostasis was observed.
Keywords: immunotoxicity; micronucleus test; pristine graphene platelets; THP-1; oxidative stress; cytotoxicity; genotoxicity